2016
DOI: 10.1016/j.jsv.2016.05.028
|View full text |Cite
|
Sign up to set email alerts
|

The influence of phase-locking on internal resonance from a nonlinear normal mode perspective

Abstract: a b s t r a c t When a nonlinear system is expressed in terms of the modes of the equivalent linear system, the nonlinearity often leads to modal coupling terms between the linear modes. In this paper it is shown that, for a system to exhibit an internal resonance between modes, a particular type of nonlinear coupling term is required. Such terms impose a phase condition between linear modes, and hence are denoted phase-locking terms. The effect of additional modes that are not coupled via phase-locking terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Specifically, our hypothesis is that the phase-unlocked branches may be neglected when the NNMs are used to interpret the forced responses of a system. The stability analysis presented in [29] exploits the special properties exhibited by the system due to its symmetry and hence cannot readily be generalized to asymmetric systems, such as the beam considered here. As such, a different approach is required to investigate the significance of the phase-unlocked NNMs.…”
Section: An Analytical Investigation Of the Two-mode Beam Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, our hypothesis is that the phase-unlocked branches may be neglected when the NNMs are used to interpret the forced responses of a system. The stability analysis presented in [29] exploits the special properties exhibited by the system due to its symmetry and hence cannot readily be generalized to asymmetric systems, such as the beam considered here. As such, a different approach is required to investigate the significance of the phase-unlocked NNMs.…”
Section: An Analytical Investigation Of the Two-mode Beam Modelmentioning
confidence: 99%
“…As such, if an internally resonant forced response is close to an NNM, that NNM must be able to transfer energy between the modes. This explains why no internally resonant responses were seen to follow the phase-unlocked backbone curves in [29], as no energy can be transferred via the fundamental components of the response.…”
Section: Phase Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This allows the inclusion of motions that are not in-unison, such as out-of-unison motion [11], but which exhibit the useful same properties as NNMs. However, it has been observed that not all NNMs appear to relate to the forced responses [12]. As such, the objective of this paper is to investigate the relationship between the forced responses and NNMs, in order to understand why some NNMs appear to have little influence on the forced response.…”
Section: Introductionmentioning
confidence: 99%